2005
DOI: 10.1002/jcp.20446
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine depletion inhibits apoptosis following blocking of survival pathways in human chondrocytes stimulated by tumor necrosis factor‐α

Abstract: Chondrocyte apoptosis can be an important contributor to cartilage degeneration, thereby making it a potential therapeutic target in articular diseases. To search for new approaches to limit chondrocytic cell death, we investigated the requirement of polyamines for apoptosis favored by tumor necrosis factor-alpha (TNF), using specific polyamine biosynthesis inhibitors in human chondrocytes. The combined treatment of C-28/I2 chondrocytes with TNF and cycloheximide (CHX) resulted in a prompt effector caspase act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 35 publications
3
54
0
Order By: Relevance
“…It was well-known that TNF-α played a vital role in the pathogenesis of OA, and participated in the progression of cartilage degeneration (29). TNF-α could induce articular chondrocytes death through promoting cell apoptosis and autophagy (30)(31)(32). Several studies also found that cell autophagy had a protective effect on chondrocytes by inhibiting cell death (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…It was well-known that TNF-α played a vital role in the pathogenesis of OA, and participated in the progression of cartilage degeneration (29). TNF-α could induce articular chondrocytes death through promoting cell apoptosis and autophagy (30)(31)(32). Several studies also found that cell autophagy had a protective effect on chondrocytes by inhibiting cell death (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…SSAT activity was assayed as previously reported (Stanic et al, 2008) and calculated as pmol/ min/mg protein. Caspase-3-like activity was measured by the cleavage of the fluorogenic peptide substrate Ac-Asp-Glu-Val-Asp-7-amido-4-methylcoumarin (Ac-DEVD-AMC) as previously detailed (Stanic et al, 2006). Since the sequence DEVD represents a substrate for caspase-3 and other effector caspases, this activity has been referred to as caspase-3-like activity.…”
Section: Determination Of Enzymatic Activities and Polyamine Contentmentioning
confidence: 99%
“…Primary cultures of chondrocytes were also used and prepared as described (Stanic et al, 2006). Chondrocytes were cultured in DMEM/F-12 medium and 10% FCS as previously detailed (Stanic et al, 2006). For experiments, growing chondrocytes were incubated in the absence or presence of 10 mM DENSPM, 10 mM spermine, 1 mM DFMO, 1 mM CGP 48664, 500 U/ml TNF, 0.2 mM CHX or other inhibitors as described in the text.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations